Double fortified salt: an effective measure to control micronutrient deficiencies in Indian pregnant women - Reddy, Kejal Joshi; Nair, Sirimavo (International Journal Of Community Medicine And Public Health, 2017)
Background: Pregnant women and children are extremely affected by micronutrient deficiencies with reference to fetal growth manifestations as well as post birth. Iodine and iron deficiency leads to poor life quality during early fetal development and young children may compromise on their IQ and cognitive development. It is reported that there is an interrelations between iron and iodine metabolism. However, references on using double fortified salt (DFS) as a tool to improve micronutrient status among pregnant women are limited; hence this study was designed. Methods:Pregnant women (n=150) were enrolled from a semi government hospital of urban Vadodara, Gujarat, India during first trimester (<12 weeks) and followed up till the end of gestation, n=75 were divided in experimental (DFS supplemented) and control (IS consumers) group. Impact on iron and iodine status was assessed by Hb concentration and UIE respectively. Results: Mean Hb improved significantly (p<0.001) (+0.42 g/dl) in experimental group and reduced insignificantly (0.20 g/dl) in control group at the end, since DFS provided additional 93 mg of iron within 6 months of supplementation. Median UIE improved insignificantly (278.6 to 299.01µg/L) in experimental group and decreased significantly (p<0.05) (376.59 to 288.66 µg/L) in control group. Conclusions:Hence, we conclude that DFS could improve iron and iodine status of experimental group compared to control group. It is an effective measure to control two essential micronutrient deficiencies together.